Discreet World of Microbes - Abdul Razak, Syarah Izzati; Idris, Fitratul Azimah; Azmi, Azny; Saad, Wan Zuhainis (UTM Academic Leadership (UTMLead), Universiti Teknologi Malaysia, 2016)
Children are always curious about everything. Let’s get the kids to be curious on what’s on them or what are they living with through playing a board game about microbes, Discreet World of Microbes will bring the children to the new adventure of learning microbes in a fun and engaging way.